2020
DOI: 10.1097/crd.0000000000000356
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Burden and Unmet Need in Recurrent Pericarditis: A Systematic Literature Review

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 59 publications
(145 reference statements)
1
5
0
1
Order By: Relevance
“…Approximately 40% of patients with RP included in this study experienced multiple recurrences, which is consistent with prior estimates (range: 24-55%) [3,11]. In some of these patients, recurrences may cause life-threatening complications such as constrictive pericarditis and cardiac tamponade [4]; a recent systematic literature review of real-world studies showed that cardiac tamponade and constrictive pericarditis occur in 12.7% and 1.84% of patients with RP (i.e., with or without multiple recurrences), respectively [18]. Furthermore, disease duration exceeded 3 years for nearly half of patients with multiple recurrences.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Approximately 40% of patients with RP included in this study experienced multiple recurrences, which is consistent with prior estimates (range: 24-55%) [3,11]. In some of these patients, recurrences may cause life-threatening complications such as constrictive pericarditis and cardiac tamponade [4]; a recent systematic literature review of real-world studies showed that cardiac tamponade and constrictive pericarditis occur in 12.7% and 1.84% of patients with RP (i.e., with or without multiple recurrences), respectively [18]. Furthermore, disease duration exceeded 3 years for nearly half of patients with multiple recurrences.…”
Section: Discussionsupporting
confidence: 84%
“…Conventional treatments fail to provide adequate symptom control and prevention of future recurrences for many patients with pericarditis. Sustained NSAIDs and systemic steroids are complicated by serious side effects [4,12,18,30,31]. Until recently, there were no FDA-approved treatments for pericarditis; rilonacept was recently approved for treatment of recurrent pericarditis and reduction in risk of recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Idiopathic recurrent pericarditis (IRP) is a poorly understood sequela of acute pericarditis that impacts significantly on quality of life. 1 , 2 , 3 IRP management remains challenging, with no US guidelines currently in place to aid clinicians and, although studies have demonstrated that corticosteroids are associated with increased recurrence risk, their use in IRP remains widespread. 1 , 2 , 3 , 4 Consequently, there is a need to understand the mechanisms driving IRP, to guide management that minimizes treatment‐associated harm.…”
Section: Tablementioning
confidence: 99%